Global governance of artificial intelligence and its reflection at the national level (some basic legal and technological aspects) - Kurmangali, M.Sh.; Korzhumbayev, R.A. (Bulletin of the Karaganda University “Law Series”, 2025)
The purpose of the article is to conduct a scientific and expert analysis of the current legal and technological aspects of global governance of artificial intelligence and its reflection at the national level using the case of Kazakhstan. The research question is to analyze global trends in the field of artificial intelligence, and to identify opportunities for Kazakhstan to participate in the processes of global governance of artificial intelligence and international cooperation in this area, as well as in the formation of policies, rules and specific measures for the development of artificial intelligence in our country. The article used qualitative research methods, as well as a literature review, synthesis, systematic review, including an analysis of international documents and current practice in the field of artificial intelligence management. The results of the study consist in the analysis and systematization of knowledge of the Global Digital Compact, in the definition of governance entities in the global digital space. The issues of reflection at the national level of global processes of artificial intelligence governance in Kazakhstan are analyzed. The issues of the artificial intelligence ecosystem, conceptual approaches to the development of national artificial intelligence are considered. The authors’ main conclusions are that in its policy on the development of artificial intelligence, Kazakhstan needs to consider both global trends and the emerging international legal framework for regulating the sphere of artificial intelligence in order to advance national interests in this area.